Professing darkness: Cormac McCarthy's Catholic critique of American enlightenment - DeCoste, D. Marcel (LSU Press, 2024)
COVER -- CONTENTS -- LIST OF ABBREVIATIONS -- ACKNOWLEDGMENTS -- INTRODUCTION. The Only Words I Know Are the Catholic Ones: McCarthy's Christian Critique of American Enlightenment -- 1 Disenchantment and Dependence: The Contending Creeds of Enlightenment and Catholicism -- 2 In This Lush Waste: Commodification, Communion, and the Sacramental Margins in Suttree -- 3 A Figure of Wretched Arrogance: Reifying Autonomy, Dehumanizing Science, and the Hope of Conversion in Outer Dark and Child of God -- 4 Properly Suzerain of the Earth: Augustinian Evil and the Unmaking of Diabolical Enlightenment in Blood Meridian -- 5 La Fe Es Todo: False Innocence and Broken Faith in the Border Trilogy -- 6 Like the Last Host of Christendom: Deadly Pragmatism, Profane Communion, and the Power of Eucharist in The Road -- CODA. The Unimaginable Penitent: Penance and the Myth of American Innocence in The Counselor, The Passenger, and Stella Maris -- NOTES -- WORKS CITED -- INDEX.